Analysis of streptococcus pneumoniae using fourier-transformed infrared spectroscopy allows prediction of capsular serotype - Burckhardt, Irene; Zimmermann, Stefan (European journal of clinical microbiology & infectious diseases, 2019)
Determination of the capsule type of clinical isolates of Streptococcus pneumoniae is a prerequisite for epidemiological studies and further vaccine development. The Quellung reaction for serotyping is expensive and mostly done in reference centres. We wanted to evaluate whether Fourier-transformed infrared (FT-IR) spectroscopy is suitable for capsular type analysis and prediction of pneumococcal serotypes. We used the IR-Biotyper™ (Bruker) to create a database containing the spectra of 120 strains from invasive disease. The strains covered the 24 vaccine serotypes contained in the 13-valent conjugate vaccine (PCV13) and the 23-valent polysaccharide vaccine (PSV23). Hierarchical clustering analysis was performed. Finally, two different classification sets were created (PCV13 and PSV23). They were used to predict the serotype of 168 different challenge strains (invasive and non-invasive disease) covering 48 different serotypes (vaccine and non-vaccine types). FT-IR spectra from pneumococci (1300-800 cm−1) clustered along their serotype as determined by the Quellung reaction (120 strains, 24 different serotypes). Strains with unknown serotype fell within the cluster of the correct serotype, as long as the latter was represented in the database (168 strains, 48 different serotypes). Concordance between the Quellung reaction and FT-IR spectroscopy was excellent (kappa ≥ 0.75). FT-IR spectroscopy is a fast and cost-effective method to predict the capsular serotype of pneumococci.
Gesehen am 29.01.2020